MUNICIPAL BOND MARKET IN UKRAINE: HISTORICAL BACKGROUND AND PROSPECTS - Kyrylenko, Olha; Luchka, Andriy; Malynyak, Bohdan (Journal of European Economy, 2005)
The paper reviews the historical background and the development of the local loans markets in Ukraine. The paper examines the municipal loans markets in other EU and Asian countries. The paper also examines the current issues of the development of the local loans market in Ukraine. The paper ends with certain suggestion for improvement in the national system for allocation of local budgets.